Neutrophil-to-lymphocyte ratio for predictor of in-hospital mortality in ST-segment elevation myocardial infarction: a meta-analysis (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND ST-segment elevation myocardial infarction (STEMI) is the most life-threatening condition of acute coronary syndrome that carries a poor prognosis of in-hospital mortality. Multiple scoring systems have been developed to predict in-hospital mortality and other cardiovascular events. Neutrophil-to-lymphocyte ratio (NLR) is hardly used as a predictor of in-hospital mortality. This study was aimed to determine the predictive value of NLR concerning in-hospital mortality in STEMI patients. METHODS Literature search and pooled analysis related to studies on MEDLINE/PubMed, EBSCO, Science Direct, Cochrane, and ProQuest were retrieved. Inclusion criteria were met if they were cohort studies, the subjects were STEMI patient, contained pretreatment NLR cut-off, and considered in-hospital mortality, which is defined as cardiac or all-cause mortality. Quality assessment was conducted using Newcastle-Ottawa scale. Review Manager version 5.3 (The Nordic Cochrane Centre, Copenhagen) was used for meta-analysis. RESULTS We found 12 studies with a total of 7,251 STEMI subjects with median NLR cut-off value of 5.6. Elevated NLR on admission carries a high risk of in-hospital mortality (odds ratio [OR] = 3.00, 95% confidence interval [CI] = 2.46–3.67). A slightly higher risk of all-cause mortality (OR = 2.74, 95% CI = 1.99–3.77) was observed compared with cardiac-related mortality (OR = 3.20, 95% CI = 2.47–4.14). No significant heterogeneity was observed between these studies (p = 0.46, I2 = 0%). CONCLUSIONS Elevated NLR predicts a higher in-hospital mortality rate of STEMI patients.